E-101 Economic impact of the first pass effect (FPE) in the treatment of stroke with the EMBOTRAP II device (in ARISE-II). (22nd July 2019) - Zaidat, O; Saver, J; Mattle, H; Bozorgchami, H; Narata, A; Yoo, A; Ribo, M; Crivera, C; Cameron, H; Andersson, T
Abstract : Introduction: The first pass effect (FPE), a measure of thrombectomy device's ability to restore near or complete revascularization (modified Thrombolysis in Cerebral Ischemia [mTICI] ≥2c) in a single pass, may be considered as a benchmark for thrombectomy devices in the treatment of acute ischemic stroke. While the FPE has been shown to be an independent predictor of good functional outcomes (modified Rankin Scale [mRS] ≤2) and is associated with reduced 90-day mortality, the economic impact of achieving the FPE has not been assessed. Methodology: Data were obtained from the EMBOTRAP II device, ARISE-II (n=227) study. FPE was defined as complete revascularization (mTICI ≥2c) after the first pass of the EMBOTRAP II device. Patients who did not achieve complete revascularization within the ARISE-II population were excluded from the analysis. Healthcare resources included total hospital length of stay (LOS), days in the intensive care unit (ICU), standard bed days, and procedural device use (stent retrievers and aspiration devices). Costs from the literature, in 2018 USD, were applied to healthcare resources. Results: In ARISE-II, 76% of patients (n=172) achieved complete revascularization; among these patients, 53% achieved the FPE. Among patients that achieved complete revascularization, baseline characteristics were well-balanced between patients that did or did not achieve the FPE. A significantly higher percentage of patients that achieved the FPE had good functional outcomes vs. those that did not achieve the FPE (80.5% vs. 61.0%, p=0.006). Healthcare resource use was lower among patients that achieved the FPE. While patients that achieved the FPE required only a single EMBOTRAP II device, 35% of the patients that did not achieve the FPE required both the EMBOTRAP II device and an additional device to achieve complete revascularization. Patients that achieved the FPE had a significantly shorter LOS (6.1 vs. 9.5 days, p=0.004) and fewer days spent in a standard bed (3.1 vs. 6.1, p=0.004) vs. those that did not achieve the FPE. Overall, the reduction in healthcare resource use associated with achieving the FPE led to estimated per-patient cost-savings of 6, 355 (table 1). In the absence of cost data reported in ARISE-II, costs for healthcare resource use were obtained from the literature, which may not be generalizable across settings and is a limitation of this analysis. Additionally, this analysis did not include all components of health resource use that may impact costs (e.g., procedure time, surgical evacuation for symptomatic intracranial hemorrhage [sICH]). Conclusion: Among patients with final complete reperfusion (mTICI≥2c), achieving the FPE may lead to per-patient cost-savings of 6, 355 due to reductions in procedural and in-patient healthcare resource use. Disclosure: O. Zaidat: 1; C; Cerenovus, Stryker, Medtronic, Penumbra, Genentech. 2; C; Stryker, Cerenovus, Penumbra, Medtronic. J. Saver: 2; C; Cerenovus, Stryker, Medtronic, Rapid Medical. 4; C; Rapid Medical. 5; C; University of California. H. Mattle: 1; C; Neuravi/Cerenovus. 2; C; Neuravi/Cerenovus. 3; C; Neuravi/Cerenovus. H. Bozorgchami: 2; C; Cerenovus, Stryker, Coherex. A. Narata: None. A. Yoo: 1; C; Cerenovus, Stryker, Medtronic, Penumbra, Genentech. 2; C; Cerenovus, Genentech, Zoll Circulation. 4; C; Insera Therapeutics. M. Ribo: 1; C; Stryker, Medtronic. 2; C; Cerenovus, Stryker, Medtronic, Anaconda Biomed. 4; C; Anaconda Biomed. C. Crivera: 4; C; Johnson & Johnson. 5; C; Johnson & Johnson. H. Cameron: 5; C; Cornerstone Research Group, contracted by Cerenovus. T. Andersson: 2; C; Cerenovus, Anaconda, Medtronic, Rapid Medical, Ablynx, Amnis Therapeutics.